2019
DOI: 10.1073/pnas.1903765116
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase inhibitors induce a BRCAness phenotype that sensitizes NSCLC to PARP inhibitor and ionizing radiation

Abstract: A minority of cancers have breast cancer gene (BRCA) mutations that confer sensitivity to poly (ADP-ribose) polymerase (PARP) inhibitors (PARPis), but the role for PARPis in BRCA-proficient cancers is not well established. This suggests the need for novel combination therapies to expand the use of these drugs. Recent reports that low doses of DNA methyltransferase inhibitors (DNMTis) plus PARPis enhance PARPi efficacy in BRCA-proficient AML subtypes, breast, and ovarian cancer open up the possibility that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 63 publications
5
57
0
Order By: Relevance
“…We and others have reported that PARPi increases DSB formation and confers radiosensitization in lung cancer models through a PARP-trapping mechanism (15,16). The work reported here suggests that DNMTi can augment PARPi radiosensitization and is a combination strategy with significant translational potential (6). The observation that AZA also down-regulates factors contributing to NHEJ, a nontemplate-dependent DSB repair pathway associated with imprecise repair, may further contribute to this effect.…”
Section: Combination Of Dnmti and Parpi Or Radiotherapy In Nsclcsupporting
confidence: 56%
See 3 more Smart Citations
“…We and others have reported that PARPi increases DSB formation and confers radiosensitization in lung cancer models through a PARP-trapping mechanism (15,16). The work reported here suggests that DNMTi can augment PARPi radiosensitization and is a combination strategy with significant translational potential (6). The observation that AZA also down-regulates factors contributing to NHEJ, a nontemplate-dependent DSB repair pathway associated with imprecise repair, may further contribute to this effect.…”
Section: Combination Of Dnmti and Parpi Or Radiotherapy In Nsclcsupporting
confidence: 56%
“…In the current report, the Rassool laboratory provides mechanistic insights into this combination effect, using ionizing radiation to initiate DNA damage in lung cancer models (6). The investigators find that DNMT inhibition abrogates both HR and nonhomologous end joining (NHEJ), 2 key complementary DSB repair pathways, in NSCLC cells.…”
Section: Combination Of Dnmti and Parpi Or Radiotherapy In Nsclcmentioning
confidence: 95%
See 2 more Smart Citations
“…Drug interaction was analyzed by the median-effect method as described by Chou-Talalay [24], as it has been extensively endorsed in the scientific literature [25][26][27][28][29]. The combination index (CI), calculated with the CalcuSyn software (Biosoft, Cambridge, UK), establishes the interaction between drugs: Synergy (CI < 1), additivity (CI = 1), or antagonism (CI > 1).…”
Section: Analysis Of Drug Interactionsmentioning
confidence: 99%